2021
DOI: 10.1155/2021/3859338
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Key Genes and Biological Pathways in Heart Failure by Integrated Bioinformatics Analysis

Abstract: Purpose. Heart failure (HF) is a clinical syndrome caused by ventricular insufficiency. In order to further explore the biomarkers related to HF, we apply the high-throughput database. Materials and Methods. The GSE21610 was applied for the differentially expressed gene (DEG) analysis. The Database for Annotation, Visualization, and Integrated Discovery (DAVID) was performed to assess Gene ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. The Gene Set Enrichment Analysis (GSEA) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For example, the Vijayakrishna Kolur team concluded that HF is related to the adaptive immune system and neutrophil degranulation by analyzing GSE141910, and obtained 10 characteristic genes 7 . Yang et al 8 analyzed GSE21610 and believed that HF is related to G protein-coupled receptor binding, peroxisome and cAMP signaling pathways, and obtained 5 characteristic genes. Therefore, our work can complement theirs to gain a more comprehensive understanding of the molecular mechanisms of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Vijayakrishna Kolur team concluded that HF is related to the adaptive immune system and neutrophil degranulation by analyzing GSE141910, and obtained 10 characteristic genes 7 . Yang et al 8 analyzed GSE21610 and believed that HF is related to G protein-coupled receptor binding, peroxisome and cAMP signaling pathways, and obtained 5 characteristic genes. Therefore, our work can complement theirs to gain a more comprehensive understanding of the molecular mechanisms of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics is a high-throughput technique, allowing high-resolution, genome-wide investigation of genetic variants, epigenetic modi cations, and associated gene expression pro les, that can screen multiple databases to identify the potential pathological biomarkers of various diseases, including cardiovascular diseases [7,8]. For example, the high-throughput RNA sequencing data has been widely employed to screen the DEGs between normal and HF samples [9,10]. And KEGG is a database resource integrated the information of genomes, biological pathways, and diseases [11,12].…”
Section: Introductionmentioning
confidence: 99%